Trade implications for vulnerable states of the global trade regime shift - Commonwealth Secretariat (World Bank WashingtonUS, 1999)
Reviews the trade policy implications for small vulnerable states of the change in the global trade regime. Suggests reasons why small vulnerable states are more likely to confront difficulties in adjusting to the new liberalised policy framework than are other countries.